Transformasi Pembelajaran Fikih Taharah melalui Metode Make A Match untuk Siswa Fase Akil Balig - Nasukah, Binti; Evi, Nur Avida (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
Understanding of Fiqh Taharah among “akil balig” students, particularly the obligation of purification after menstruation and ihtilam, remains low and poses a crucial challenge in basic Islamic education. This study examines the effectiveness of the Make a Match method, a cooperative card-matching strategy, in improving learning motivation and learning outcomes in Fiqh Taharah. A quantitative approach with a pre-experimental one-group pretest-posttest design was employed, involving 32 students. Motivation was measured through observations using a Guttman scale with five indicators, while learning outcomes were assessed using a 10-item multiple-choice test. The learning process was conducted over three meetings covering the concepts of menstruation/ihtilam, related prohibitions, and purification intention, supported by group discussions and presentation of matching results. The findings showed an increase in motivation from 70% to 90% on the first day and stabilization at 85% on the second and third days, with an N-Gain of 0.608 (medium category). The average pretest score of 53.125 increased to 73 on the posttest (N-Gain 0.511), confirmed as significant by the Wilcoxon test (p = 0.000). The instruments were proven valid and reliable. These results indicate that the Make a Match method is effective in enhancing motivation and understanding of Fiqh Taharah among “akil balig” students and provide recommendations for madrasah teachers to adopt this innovation to overcome the limitations of traditional methods, enrich the Islamic education curriculum, and extend its use to other fiqh.